2022
DOI: 10.3390/jof8070726
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the M36 Metalloprotease FgFly1 in Fusarium graminearum

Abstract: Fungalysin metallopeptidase (M36), a hydrolase, catalyzes the hydrolysis of alanine, glycine, etc. Normally, it is considered to play an important role in the progress of fungal infection. However, the function of fungalysin metallopeptidase (M36) in Fusarium graminearum has not been reported. In this study, we explored the biological functions of FgFly1, a fungalysin metallopeptidase (M36) of F. graminearum. We found that ΔFgFly1 did not affect the ability to produce DON toxin, although it inhibited spore ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…During the coevolution of plants and pathogens, a complex interaction relationship develops. Plants have evolved various recognition and resistance mechanisms to organize and limit pathogen infection, while pathogens have developed diverse pathogenic mechanisms to avoid or overcome plant resistance mechanisms [37]. So far, we have only confirmed that FgEps1 is involved in the pathogenesis of F. graminearum but have not yet analyzed its mode of action in this process.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…During the coevolution of plants and pathogens, a complex interaction relationship develops. Plants have evolved various recognition and resistance mechanisms to organize and limit pathogen infection, while pathogens have developed diverse pathogenic mechanisms to avoid or overcome plant resistance mechanisms [37]. So far, we have only confirmed that FgEps1 is involved in the pathogenesis of F. graminearum but have not yet analyzed its mode of action in this process.…”
Section: Discussionmentioning
confidence: 86%
“…Once the aerial mycelium had grown over the culture dish, the aerial mycelium was scraped off, and 500 µL of 2.5% Tween-20 solution was added. The dish was then incubated for 15 days at 25 • C, alternating between dark and light cycles every 12 h [37]. The ascospore shell and ascospore morphology were observed under the light microscope.…”
Section: Sexual Reproductionmentioning
confidence: 99%
“…Among the virulence factors of phytopathogenic microorganisms, many proteins with metallopeptidase activity have been described [44][45][46][47][48][49][50][51][52][53][54]. Most of these virulencerelated metallopeptidases are considered "instruments" of brute force that contribute to the disintegration of plant tissues, providing non-specific, extensive digestion of host proteins [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Herewith, in the presence of the specific host R protein, Avr-Pita acts as a race-specific elicitor that triggers a hypersensitive response associated with full plant resistance [53]. FgFly1 metallopeptidase from Fusarium graminearum interacts with the calmodulin-binding transcription activator, inhibiting the SA-mediated immune response [54].…”
Section: Discussionmentioning
confidence: 99%